CYBER ATTACK AN INVISIBLE WAR AGAINST NATIONS: ISSUES & OPTIONS (International Journal of Food and Nutritional Sciences, 2022)
the Internet has provided a new delivery mechanism that can increase the speed, scale, and power of an attack on the national security and integrity of the nation. The threat is so potent that its impact is horrible than any act of terrorism. Cyber warfare attacker affect national critical infrastructures, including everything from elections to electricity. This paper intends to examine the intensity of threat relating to cyber attacks against the nation. It also evaluates the countries policy as well as the technological challenges in addressing threat. The researcher summed up that aalthough the government can play a key role in protecting such systems (e.g., through the development of policies, standards, and law enforcement), it can do little without support technological infrastructure and global cooperation.